Effects of different levels of end-expiratory pressure on hemodynamic, respiratory mechanics and systemic stress response during laparoscopic cholecystectomy - Sen,Oznur (2017)
Abstract Objective: General anesthesia causes reduction of functional residual capacity. And this decrease can lead to atelectasis and intrapulmonary shunting in the lung. In this study we want to evaluate the effects of 5 and 10 cmH2O PEEP levels on gas exchange, hemodynamic, respiratory mechanics and systemic stress response in laparoscopic cholecystectomy. Methods: American Society of Anesthesiologist I-II physical status 43 patients scheduled for laparoscopic cholecystectomy were randomly selected to receive external PEEP of 5 cmH2O (PEEP 5 group) or 10 cmH2O PEEP (PEEP 10 group) during pneumoperitoneum. Basal hemodynamic parameters were recorded, and arterial blood gases (ABG) and blood sampling were done for cortisol, insulin and glucose level estimations to assess the systemic stress response before induction of anesthesia. Thirty minutes after the pneumoperitoneum, the respiratory and hemodynamic parameters were recorded again and ABG and sampling for cortisol, insulin, and glucose levels were repeated. Lastly hemodynamic parameters were recorded; ABG analysis and sampling for stress response levels were taken after 60 minutes from extubation. Results: There were no statistical differences between the two groups about hemodynamic and respiratory parameters except mean airway pressure (P mean). P mean, compliance and PaO2; pH values were higher in 'PEEP 10 group'. Also, PaCO2 values were lower in 'PEEP 10 group'. No differences were observed between insulin and lactic acid levels in the two groups. But postoperative cortisol level was significantly lower in 'PEEP 10 group'. Conclusion: Ventilation with 10 cmH2O PEEP increases compliance and oxygenation, does not cause hemodynamic and respiratory complications and reduces the postoperative stress response.